Design of customizable devices for cutaneous drug delivery and diagnosis - Wong, Sammi Xue Yi (Nanyang Technological University, 2024)
Background: Skin biopsies are routinely used for diagnosing skin diseases and malignancies, employing techniques like shave, punch, incisional, and excisional biopsies. While effective, these methods can be invasive and result in scarring and discomfort. Microneedle (MN) biopsies, enabled by advancements in 3D printing, offer a less invasive alternative, potentially reducing pain and scarring. However, MNs may not yield samples suitable for histopathological diagnosis. Molecular-level analysis, particularly Next-Generation Sequencing (NGS), presents opportunities for precise diagnoses with minimal tissue samples. Objective of Project: The aim is to create a minimally invasive biopsy method capable of extracting quantifiable amounts of DNA for molecular-level analysis while mitigating the limitations of traditional biopsies. Results and Discussion: Amongst all the tested MN geometries, Design 15 achieved 93.75% penetration rate, extracted 1501.67 ± 102.659 ng of DNA and 2750000 cells. Optimized configurations of Design 15 (D15-4-9, D15-16-6, D15-16-9, and D15-9-6) were observed to extract an average of 2761.195 ng of DNA and 135416.665 cells. Conclusion: The optimized MN geometry, Design 15 displayed satisfactory results. By optimizing MN density and quantity of patches, certain optimized configurations of Design 15 were able to produce results comparable to traditional biopsies suggesting its potential in serving as an alternative to conventional biopsy methods. Future Works: Mechanical properties of the studied 3D-printed MNs can be studied. The trials can also be expanded to include fresh human skin for more accurate results. Additionally, incorporating next-generation sequencing (NGS) applications could reveal the potential for molecular fingerprinting of skin diseases.